Perioperative Management of Chronic Kidney Disease Patients with Bowel Perforation - Hafizh Nur Santoso; Dykall Naf'an Dzikri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2022)
Background: Anesthesia management applied during surgery in patients with chronic kidney disease (CKD) is different from ordinary anesthetic management. It is known that currently, there are not many case reports discussing anesthetic management in patients with CKD.Case Illustration: A 70-year-old patient with abdominal colic et causa abdominal perforation complained of abdominal pain accompanied by heavy bowel movements and flatus throughout the abdominal area. The patient was anesthetized by regional anesthesia with local agent bupivacaine and treated with laparotomy. Bupivacaine is the first local anesthetic drug with an acceptable onset of action, long duration of action, and a tendency for the sensory block to be greater than its motor block.Conclusion: This case report explains the novelty of anesthetic management of CKD patients undergoing exploratory laparotomy surgery using the reported patient cases. Operations in patients with CKD are preferable to regional anesthesia.